2020
DOI: 10.1016/j.cub.2020.06.066
|View full text |Cite
|
Sign up to set email alerts
|

Ecology: The Patagonian Sun Dance

Abstract: Stable isotope and band-encounter analysis delineate migratory patterns and catchment areas of whitethroated sparrows at a migration monitoring station. Oecologia 144, 541-549. 13. DeWolfe, B.B., and Baptista, L.F. (1995).Singing behavior, song types on their wintering grounds and the question of leap-frog migration in puget sound white-crowned sparrows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Nevertheless, annual or seasonal rainfall in aridlands are generally poor predictors of above‐ground litter decomposition (Austin, 2011; Meentemeyer, 1978; Vanderbilt et al., 2008), and various studies have demonstrated no response of above‐ground litter decomposition to water pulses, drought or nutrient addition (Austin et al., 2009; Austin & Vivanco, 2006; Kemp et al., 2003; Moorhead & Reynolds, 1989; Whitford et al., 1986). As a result, this ecological incongruency has led to the exploration of new controls on above‐ground C turnover (Austin, 2011; Barnes et al., 2015; Berenstecher et al., 2020; King et al., 2012; Pérez‐Harguindeguy, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, annual or seasonal rainfall in aridlands are generally poor predictors of above‐ground litter decomposition (Austin, 2011; Meentemeyer, 1978; Vanderbilt et al., 2008), and various studies have demonstrated no response of above‐ground litter decomposition to water pulses, drought or nutrient addition (Austin et al., 2009; Austin & Vivanco, 2006; Kemp et al., 2003; Moorhead & Reynolds, 1989; Whitford et al., 1986). As a result, this ecological incongruency has led to the exploration of new controls on above‐ground C turnover (Austin, 2011; Barnes et al., 2015; Berenstecher et al., 2020; King et al., 2012; Pérez‐Harguindeguy, 2020).…”
Section: Introductionmentioning
confidence: 99%